Academic apartheid: race and the criminalization of failure in an American suburb - Drake, Sean J. (University of California Press, 2022)
Introduction : segregated schools and disadvantaged students in an affluent neighborhood -- "If you're not in AP classes, then who are you?": how pinnacle's institutional culture stratified the student body -- The symbolic criminalization of failure -- the segregation of teaching and learning -- The institutionalization of ethnic capital -- "We've failed these kids" : missed opportunities and signs of hope -- Conclusion -- Methodological postscript.